Australasian Public Awareness and Belief in Conspiracy Theories: Motivational Correlates. Issue 1 (16th March 2021) - Marques, Mathew D.; Ling, Mathew; Williams, Matt N.; Kerr, John R.; McLennan, Jim
Abstract : Belief in conspiracies is not restricted to the fringe dwellers of society. International research suggests that such beliefs are quite common and that conspiracy theories may serve three basic psychological motives (i.e., epistemic, existential, and relational) for individuals. Yet, little is known about conspiracy theory awareness or belief in Australasia. We report the first large systematic investigation of system‐justifying motives using two nationally representative samples of Australians ( n  = 1011) and New Zealanders ( n  = 754). Our findings show that almost all are aware of local and international conspiracies, the majority endorse one or more, and that all three psychological motives consistently relate to conspiracy belief, but not to awareness. In a series of hierarchical multiple regressions, we find that relational (i.e., increased anomie and disillusionment with the government) and existential motives (i.e., less trust in others and increased religiosity) are uniquely and relatively more important than epistemic needs (i.e., decreased analytic thinking) as predictors of increased local and international conspiracy belief. Findings are discussed in terms of the importance of understanding conspiracy theories as an ideological belief system that may function to serve underlying psychological motives.